Does Diabetes Mellitus Alter the Onset and Clinical Course of Vascular Dementia? - Santosh B. Murthy; Ali Jawaid; Salah U. Qureshi; Yogeshwar Kalkonde; Andrew M. Wilson; Michael L. Johnson; Mark E. Kunik; Paul E. Schulz (Behavioural Neurology)
Background: Vascular dementia (VaD) is the second most common dementing illness. Multiple risk factors are associated with VaD, but the individual contribution of each to disease onset and progression is unclear. We examined the relationship between diabetes mellitus type 2 (DM) and the clinical variables of VaD.